Effects of ovulation induction agents on ovarian surface epithelium in rats - Ozcan, Zeynep; Celik, Husnu; Gurates, Bilgin; Ozercan, Hanifi Ibrahim; Hanay, Fethi; Nalbant, Mehmet; Dogan, Zeynep (Elsevier Sci Ltd, 2009)
The aim of this Study was to examine the effects of ovulation induction agents on the ovarian Surface epithelium in rats. Sixty adult females were randomly divided into six groups, each containing 10 rats. In four of these groups ovulation induction was applied with six cycles of clomiphene citrate, human menopausal gonadotrophin (HMG), recombinant FSH (rFSH) or human chorionic gonadotrophin (HCG), respectively, followed by unilateral oophorectomy, and another six cycles of the same treatment. After a total of 12 cycles of ovulation induction, the remaining ovary was taken out and the alterations in ovarian surface epithelium were examined. No malignancies were observed on the ovarian surface epithelium of the rats that were given clomiphene citrate, rFSH or HMG as ovulation induction agents, while identification rates of histopathological parameters constituting epithelial dysplasia were found to be significant (P < 0.05). There was no significant dysplasia in the epithelium of the group which was given HCG only, relative to control groups. The findings suggest that the ovulation induction agents except for HCG bring about dysplasia in the ovarian surface epithelium. It is not clear whether these dysplasias are precursory lesions of ovarian malignancies.
Keywords: infertility; ovarian epithelial carcinoma; ovarian epithelial dysplasia; ovarian surface epithelium; ovulation induction